Tata Kelola Sistem Informasi Jadwal Praktik Dokter Berbasis Web dengan Menggunakan Framework Laravel - Hendiawati, Yupitasari; Abdussalaam, Falaah; Gunawan, Erix (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Doctor Practice Schedule is one of the important components needed in every health care facility. Scheduling that is fairly conventional by still using Ms.Excel, as well as the lack of accurate information about the schedule of which doctors are practicing or doctors whose services are full become obstacles for patients who will seek treatment. Therefore, it is proposed to design an information system to improve the quality of service more effectively and efficiently. The design of this web-based doctor schedule information system aims to make it easier for patients to see information on doctor practice schedules and appointments digitally. This research uses qualitative research with a descriptive approach. The development method used is the waterfall model with data collection techniques through observation and literature study, which is designed using the PHP programming language with the Laravel framework and MySQL as a storage database. The results of this study, with a website-based system, patients and prospective patients can see the doctor's practice schedule and appointment online anytime, anywhere and by anyone through a browser such as google chrome connected via the internet network. So that patients do not need to come to the hospital if they only want to see the doctor's schedule.